PROCESS IMPROVEMENT USING QUALITATIVE ANSWERS BY MEANS OF NEURONAL NETWORKS - Cevallos Ampuero, Juan (2005)
The article deals with the application of Neural Networks in parameters optimization problems for the improvement of processes in which the answers of quality are qualitative. We propose a methodology to improve the quality of processes using neural networks and present an application of neural networks in the solution of problems in which the answers of quality are qualitative.